Effects of early intense bombardment on megaregolith evolution and on lunar (and planetary) surface samples. (18th December 2020) - Hartmann, William K.; Morbidelli, Alessandro
Abstract: Impact rates in the first 500 Myr of the solar system are critical to an understanding of lunar geological history, but they have been controversial. The widely accepted, post‐Apollo paradigm of early lunar impact cratering (about 1975–2014) proposed very low or negligible impact cratering in the period from accretion (>4.4 Ga) to 4.0 Ga ago, followed by an 170 million year long spike of cataclysmic cratering, during which most prominent multi‐ring impact basins formed at age 3.9 Ga. More recent dynamical models suggest very early intense impact rates, declining throughout the period from accretion until an age of 3.0 Ga. These models remove the basin‐forming spike. This shift has important consequences vis‐à‐vis megaregolith evolution and properties of rock samples that can be collected on the lunar surface today. We adopt the Morbidelli et al. (2018) "accretion tail" model of early intense bombardment, declining as a function of time. We find effects differing from the previous models: early crater saturation and supersaturation; disturbance of magma ocean solidification; deep early megaregolith; and erosive destruction of the earliest multi‐ring basins, their impact melts, and their ejecta blankets. Our results explain observations such as differences in numbers of early lunar impact melts versus numbers of early igneous crustal rocks, highland breccias containing impact melts as old as 4.35 Ga, absence of a 170 Myr long spike in impact melt ages at 3.9 Ga among lunar and asteroidal meteorites, and GRAIL observations of lunar crustal structure.